2013
DOI: 10.1007/s00595-013-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastric conduit-preserving, radical pancreaticoduodenectomy with microvascular reconstruction for pancreatic head cancer after esophagectomy: report of a case

Abstract: Pancreaticoduodenectomy is a radical treatment for pancreatic head cancer. However, it is sometimes difficult to perform pancreaticoduodenectomy, particularly in patients who have previously undergone esophagectomy with gastric conduit reconstruction. We herein describe a surgical technique for radical pancreaticoduodenectomy with microvascular reconstruction that preserves the gastric conduit. A 72-year-old male with a previous history of esophagectomy and gastric conduit reconstruction for esophageal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…With the relatively higher risk of postoperative local recurrence of pancreatic head cancer compared to other periampullary cancers, more careful consideration is required for GDA preservation. Inoue et al [ 8 ] reported that, for the pancreatic head cancer patient with suspected GDA invasion after surgery for esophageal cancer, the GDA was resected and microscopic vascular reconstruction was performed with anastomosis of the RGEA to the GDA stump and the RGEV to the left renal vein to maintain the blood circulation of the gastric tube.…”
Section: Discussionmentioning
confidence: 99%
“…With the relatively higher risk of postoperative local recurrence of pancreatic head cancer compared to other periampullary cancers, more careful consideration is required for GDA preservation. Inoue et al [ 8 ] reported that, for the pancreatic head cancer patient with suspected GDA invasion after surgery for esophageal cancer, the GDA was resected and microscopic vascular reconstruction was performed with anastomosis of the RGEA to the GDA stump and the RGEV to the left renal vein to maintain the blood circulation of the gastric tube.…”
Section: Discussionmentioning
confidence: 99%
“…Other challenging options when the right gastroepiploic vessels are compromised include the use of supercharged jejunal interposition conduits [7] or microvascular reconstruction methods for the right gastroepiploic vessels [8, 9]. Oesophagogastrectomy and pancreaticoduodenectomy are individually extensive operations, and their combination either simultaneously or metachronously poses unique challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a typical pancreaticoduodenectomy (PD) would require ligating the GDA, but in the setting of previous esophagectomy that would compromise the viability of the gastric conduit. Inoue et al in a recently published case report describes three different techniques previously used to overcome this technical challenge [3] . (A) PD with preservation of the GDA/GEA, (B) PD with division of the GDA/GEA and microvascular anastomosis, (C) PD with resection of the gastric conduit and reconstruction with small bowel or colon.…”
Section: Discussionmentioning
confidence: 99%
“…(A) PD with preservation of the GDA/GEA, (B) PD with division of the GDA/GEA and microvascular anastomosis, (C) PD with resection of the gastric conduit and reconstruction with small bowel or colon. Each technique has advantages and disadvantages and differ in indications, length of operation, and oncologic outcomes [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation